2018
DOI: 10.1038/s41426-018-0029-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the pathogenic potential of highly pathogenic avian influenza (HPAI) H5N6, and H5N8 viruses isolated in South Korea during the 2016–2017 winter season

Abstract: Highly pathogenic avian influenza (HPAI) A(H5N6) and A(H5N8) virus infections resulted in the culling of more than 37 million poultry in the Republic of Korea during the 2016/17 winter season. Here we characterize two representative viruses, A/Environment/Korea/W541/2016 [Em/W541(H5N6)] and A/Common Teal/Korea/W555/2017 [CT/W555(H5N8)], and evaluate their zoonotic potential in various animal models. Both Em/W541(H5N6) and CT /W555(H5N8) are novel reassortants derived from various gene pools of wild bird viruse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 37 publications
5
48
0
Order By: Relevance
“…A low infectious dose of 10 2 TCID 50 /animal resulted in a mortality of 60%, while animals receiving higher dosages had to be euthanized before 10 dpi. The final calculated mean lethal dose 50 for the Balb/c mouse experiments was 2.4 × 10 2 /animal, demonstrating clearly a more virulent phenotype than reported previously for H5N8A viruses by others 18 , 54 . Whether this variability reflects different experimental designs e.g., age of the mice, endpoint criteria or represents different molecular determinants of influenza virus pathogenesis in mice will be part of future studies.…”
Section: Discussionmentioning
confidence: 52%
“…A low infectious dose of 10 2 TCID 50 /animal resulted in a mortality of 60%, while animals receiving higher dosages had to be euthanized before 10 dpi. The final calculated mean lethal dose 50 for the Balb/c mouse experiments was 2.4 × 10 2 /animal, demonstrating clearly a more virulent phenotype than reported previously for H5N8A viruses by others 18 , 54 . Whether this variability reflects different experimental designs e.g., age of the mice, endpoint criteria or represents different molecular determinants of influenza virus pathogenesis in mice will be part of future studies.…”
Section: Discussionmentioning
confidence: 52%
“…Building upon earlier work on H5 viruses that caused outbreaks in Korea in 2013–2014, two isolates from the 2016–2017 winter season were evaluated for their zoonotic potential [ 103 ]. Specifically, A/environment/Korea/W541/2016 (H5N6) and A/common teal/Korea/W555/2017 (H5N8) were studied as representative H5N6 and H5N8 strains.…”
Section: Molecular Changes and The Potential For Airborne Transmismentioning
confidence: 99%
“…Neither virus transmitted to respiratory contacts, and none of the direct contact animals became infected with A/common teal/Korea/W555/2017 (H5N8); however, three of three direct contact animals shed the A/environment/Korea/W541/2016 (H5N6) virus. Given the propensity for limited transmission, receptor-binding studies were performed and revealed that both viruses had a strong α2,3-SA acid preference, although low-level binding to α2,6-SAs was also observed [ 103 ]. In response to case reports of human infections with H5N6 viruses in China, an additional Korean isolate A/mandarin duck/Korea/K16-187-3/2016 (H5N6) was also evaluated in the ferrets.…”
Section: Molecular Changes and The Potential For Airborne Transmismentioning
confidence: 99%
“…As mentioned in the EFSA report for November 2017 -February 2018 (EFSA et al, 2018c), two novel HPAI A(H5N6) reassortants are cocirculating in Asia:(1) the zoonotic reassortant belonging to clade 2.3.4.4c that was detected in domestic and wild birds in China, Japan, Myanmar, the Philippines, South Korea, Taiwan and Viet Nam, and (2) a reassortant associated with clade 2.3.4.4b that is mainly circulating in Eurasia(Kwon HI et al, 2018;Lee et al, 2018a).New cases of the zoonotic reassortant of HPAI A(H5N6) (2.3.4.4c) were reported from China and Viet Nam between 16 August and 15 November 2018(Figure 11). HPAI A(H5N6) 4.4.2.1.…”
mentioning
confidence: 99%
“…an updated nomenclature of clade 2.3.4.4 viruses is pending, the four genetic groups (a, b, c, d) of clade 2.3.4.4 introduced by Lee et al (2018a) are used in this section to give a better insight onto the characteristics of the HPAI A(H5N6) viruses detected in domestic and wild birds.As mentioned in the EFSA report for November 2017 -February 2018(EFSA et al, 2018c), two novel HPAI A(H5N6) reassortants are cocirculating in Asia: (1) the zoonotic reassortant belonging to clade 2.3.4.4c that was detected in domestic and wild birds in China, Japan, Myanmar, the Philippines, South Korea, Taiwan and Viet Nam, and (2) a reassortant associated with clade 2.3.4.4b that is mainly circulating in Eurasia(Kwon HI et al, 2018;Lee et al, 2018a).New cases of the zoonotic reassortant of HPAI A(H5N6) (2.3.4.4c) were reported from China and Viet Nam between 16 August and 15 November 2018 (…”
mentioning
confidence: 99%